The Effect of Realistic Mathemathic Education (RME) Assisted by Number Hours on Learning Achievement in The Summing Operations Material in Class I SDN Batulawang - Nida Nurhanifa; Budi Hendrawan; Anggia Suci Pratiwi (Jurnal Sekolah Dasar, 2020)
Mathematics learning is learning that develops student creativity to improve thingking skills, construct new knowledge to increase good mastery of mathematical material. In learning mathematics there are several obstacles, namely low student achievement, lack of student motivation and students still think that mathematics is difficult and difficult to learn. To overcome these obstacles there is a solution for learning mathematics that is using Realistic Mathematic Education (RME) assisted by the number of hours in the addition operation material. By using Realistic Mathematic Education (RME) assisted by number hours, it is expected to be able to improve student learning achievement in the addition operation material at SDN Batulawang. This research uses quantitative research using quasi experimental methods with the Nonequivalent Control Group Design. This research was conducted in SDN Batulawang with a population of thirty people and used a systematic sample that divided students into two classes using even odd numbers, so that the control class was fifteen people and the experimental class fifteen people. Data collection techniques were carried out through pretest and posttest. Data were analyzed using SPSS.